Answer:
(2, - 6 )
Step-by-step explanation:
Given the 2 equations
x =
y + 5 → (1)
2x + 3y = - 14 → (2)
Substitute x =
y + 5 into (2)
2(
y + 5 ) + 3y = - 14 ← distribute and simplify left side
y + 10 + 3y = - 14
4y + 10 = - 14 ( subtract 10 from both sides )
4y = - 24 ( divide both sides by 4 )
y = - 6
Substitute y = - 6 into (1) for corresponding value of x
x = (0.5 × - 6 ) + 5 = - 3 + 5 = 2
Solution is (2, - 6 )
3 remainder of 7 i fink
Step-by-step explanation:
Answer:
Hello
Step-by-step explanation:
the Pythagoras Theorem proves this
Answer:
2/10
Step-by-step explanation:
it identifed it for you in the 10's place